PEMANFAATAN PROTOKOL HTTP PADA SISTEM MONITORING SUHU AIR MENGGUNAKAN WEBSITE BERBASIS INTERNET OF THINGS (IoT) - Sofiumayroh, Hamidah; Hasfani, Hirzen (Coding: Jurnal Komputer dan Aplikasi, 2024)
The bathroom is a basic necessity for personal hygiene, yet many still use conventional methods. This research aims to determine the delay between the sensor reaching the set temperature and the data being sent to the system, as well as the effect of the number of heaters on the duration of heating the bathwater temperature. The system is designed using an Arduino WiFi R4 microcontroller and a DS18B20 temperature sensor to measure the bathwater temperature. Temperature data is sent to the server via the HTTP protocol when the temperature reaches the threshold value of 37 °C to 40 °C. The research results show that the average delay between the DS18B20 temperature sensor reaching the recorded temperature and the time the data is received by the system varies depending on the number of heaters used. With 1 heater, the average delay is 1958.33 ms. This delay increases with the addition of heaters, becoming 2574.995 ms with 2 heaters, 2599.995 ms with 3 heaters, and 3766.665 ms with 4 heaters. Adding heaters speeds up the water heating process. With 1 heater, the longest duration reaches 10 minutes 1.58 seconds at a temperature of 40 °C. This duration decreases to 6 minutes with 2 heaters, 5 minutes 17 seconds with 3 heaters, and 1 minute 45 seconds with 4 heaters. This system is capable of providing a response in reaching the target temperature as well as managing and delivering temperature information in real-time on an Internet of Things (IoT)-based website.